Catalytic Semireduction of Internal Alkynes with All‐Metal Aromatic Complexes. Issue 20 (3rd September 2015) - Deyris, Pierre‐Alexandre; Cañeque, Tatiana; Wang, Yanlan; Retailleau, Pascal; Bigi, Franca; Maggi, Raimondo; Maestri, Giovanni; Malacria, Max
Abstract A simple catalytic method involving all‐metal aromatic frameworks as precatalysts ensures an efficient route to (Z)‐alkenes. Aromatic triangular palladium clusters were used to reduce internal alkynes without any trace of the formation of alkane side products. These trinuclear complexes provide a catalytic system that parallels the activity and selectivity of their best mononuclear peers, and the catalyst likely operates through complementary mechanisms.